Comparison of LTE-A network performance using inter-band carrier aggregation method - Budiyanto, Setiyo; Silalahi, Lukman Medriavin; Simanjuntak, Imelda Uli Vistalina; Rochend, Agus Dendi; Hamid, Abdul; Wulan, Febryyanti Nawang (2024)
The focus of this research lies within a potential market segment within West Java Province, necessitating efficient data services. The research originated from customer grievances, prompting the identification and retrieval of traffic data, revealing suboptimal performance of LTE networks in the area. To address this issue, the research explores the implementation of the inter-band carrier aggregation method on LTE-Advanced networks. This method combines a 10 MHz bandwidth from Band 1 (2100 MHz) and Band 3 (1800 MHz). Implementing this approach offers a solution to augment network capacity in densely populated areas by maximizing operator resources. Simulation of this method entails two scenarios: one with Band 3 (1800 MHz) as the primary component carrier and another with Band 1 (2100 MHz) in the same role. Utilizing Atoll 3.3 software for simulation, the results indicate that carrier aggregation leads to increased average RSRP, SINR, and throughput, thereby showcasing its efficacy in enhancing network performance.